PERSEPSI MASYARAKAT TERHADAP KEBUTUHAN DAN EFEKTIVITAS BANTUAN AIR BERSIH PADA TIGA KAMPUNG DI SUMBA BARAT - Baiwu, Fredrik Lepa; Zuryani, Nazrina; Kebayantini, Ni Luh (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT The limited rainfall experienced by Desa Patiala Bawa and Desa Waimangoma causes limited water resources to meet the needs of clean water for drinking, cooking, washing, bathing and other water needs. This research aims at examining public perceptions of the needs and effectiveness of clean water assistance in three villages in West Sumba. The research method used in this study is quantitative research using primary and secondary data sources. The number of samples used as many as 104 respondents are allocated based on the Slovin formula. The data were collected using questionnaires consisting of 26 questions. Data analysis techniques used are simple linear regression analysis, productmoment correlation and coefficient of determination. Based on results indicate that the factors that influencing public perception of clean water requirement is because of the need for drinking water, toilets, washing clothes, cleaning eating feding, for livestock and watering plants with regression coefficient of 0.238 increase the clean water needs also increasing the adaptation needs for people. The level of effectiveness of clean water aid in community perception in three villages is moderate. The majority of respondents have been satisfied with clean water assistance, besides being able to provide better adaptation that has been adequate for the community. So that the government is expected to have coordination with volunteers who are willing to provide assistance to. The volunteers are not always expected to continue to provide assistance. However, as Ife said (2016) it is the community participation to find new water sources to self-build it and at the same time maintaining and conserving the clean water facilities has been provided so that they can survive for long periods of time. Keywords: public perception, clean water needs, adaptation of needs, aid effectiveness